An automatic diagnosis system based on thyroid gland: ADSTG - Dogantekin, Esin; Dogantekin, Akif; Avci, Derya (Pergamon-Elsevier Science Ltd, 2010)
In this paper, the automatic diagnosis system based on thyroid gland (ADSTG) method is introduced for diagnosis of thyroid disease. The structure of this ADSTG diagnosis system for thyroid diseases contains three stages. In first stage, the feature reduction is performed by using Principle Component Analysis (PCA) method. In second stage, the classification by using Least Square Support Vector Machine (LS-SVM) classifier. In third stage, the performance evaluation of this ADSTG method for diagnosis of thyroid disease is estimated by using classification accuracy, k-fold cross-validation, and confusion matrix methods respectively. The classification accuracy of this ADSTG diagnosis system for thyroid diseases was obtained about 97.67%. (C) 2010 Published by Elsevier Ltd.
Keywords: Thyroid gland; Principle Component Analysis (PCA); Least Square Support Vector Machine; classifier (LS-SVM); Automatic diagnostic system; Classification accuracy; k-Fold cross-validation; Confusion matrix